Batas-batas Penggunaan AI: Pendekatan Filsafat Utilitarianisme, Deontologi, dan Nicomachean Ethics dalam Konteks Pendidikan - Wahyudi, Antono (Theologia in Loco, 2025)
The use of Artificial Intelligence (AI) through outline-based prompt engineering, referred The emergence of outline-based prompt engineering — referred to in this study as Prompting Outline Production — has produced troubling phenomena in academic environments, such as claims of “writing 300 pages in three weeks, ready to publish.” Despite growing concern, the ethical dimensions of this practice have not yet been examined systematically through a comprehensive framework of ethical philosophy. This study aims to analyze the ethical limits of Prompting Outline Production through three philosophical perspectives: utilitarianism, deontology, and virtue ethics. Drawing on a literature review and Gadamer’s philosophical-hermeneutical method of horizon fusion applied to the thought of Jeremy Bentham, Immanuel Kant, and Aristotle — and reinforced by Robert Nozick’s concept of the experience machine — the study finds that utilitarianism and deontology yield neutral verdicts on Prompting Outline Production and are therefore insufficient as determinants of its ethical limits. Virtue ethics and the experience machine concept, by contrast, identify two essential ethical boundaries: rationality as the natural function of the human person, and authentic experience as existential meaning-making. From these two boundaries, the study identifies three distinct areas of AI use — reference searching, data processing, and outline development — each carrying a different ethical categorization. These findings offer a conceptual foundation for revising AI use policies in educational institutions, particularly in building a regulatory framework rooted in the values of human formation rather than mere productive efficiency.